(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Stunting is enough problems quaint for developing countries including Indonesia. The reason is that stunting is a problem of chronic malnutrition. This caused intake deficiency nutrition in children, especially toddlers, for quite a long time. Practically, the Can result in disturbances in growth nutrition in children, starting with more height short from standard as well as no weight growth. efficacy and also mental health improvement from a moderate mother’s breast-feeding role alone. Study This is its own objective. To use knowledge about influence from efficacy self and mental health coaching against behavior from the mother inside prevention stunting problem. The method of research used is quasi-experimental, with a pre-test, post-test, and control group design. The result of the study showed a difference in behavior as well as efficacy before as well as after treatment in the second group with a p value of 0.05. Study This gives the conclusion that there is influence from mental health coaching and also modules on behavior and efficacy from self to mother.